Sorcerer’s apprentices at work - Bizzarri, Mariano (Organisms. Journal of Biological Sciences, 2018)
Heritable human genetic modifications pose serious risks, and the therapeutic benefit still dubious. Therefore, there are concerns regarding the ethical and safety implications of this research as well as the negative impact it could have on studies involving the use of genome-editing techniques in non-reproductive (somatic) cells.